2015
DOI: 10.1002/smll.201502306
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the Direct and Indirect Biological Effects of ZnO Nanoparticles Using a Communicative Dual Cell‐Type Tissue Construct

Abstract: While matter at the nanoscale can be manipulated, the knowledge of the interactions between these nanoproducts and the biological systems remained relatively laggard. Current nanobiology study is rooted on in vitro study using conventional 2D cell culture model. A typical study employs monolayer cell culture that simplifies the real context of which to measure any nanomaterial effect; unfortunately, this simplification also demonstrated the limitations of 2D cell culture in predicting the actual biological res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…The serum in the medium is known to rapidly bind to the NPs and form a protein corona around the NPs 5 36 . This protein corona further helps the NPs to disperse by providing steric hindrance and electrostatic repulsion between NPs 37 38 . The absorption of protein on the NP surface not only affects the size and physical properties of NP but also affects the interaction of NPs with cellular systems.…”
Section: Resultsmentioning
confidence: 99%
“…The serum in the medium is known to rapidly bind to the NPs and form a protein corona around the NPs 5 36 . This protein corona further helps the NPs to disperse by providing steric hindrance and electrostatic repulsion between NPs 37 38 . The absorption of protein on the NP surface not only affects the size and physical properties of NP but also affects the interaction of NPs with cellular systems.…”
Section: Resultsmentioning
confidence: 99%
“…Strategies have further been investigated to integrate blood vessels into engineered tissues including the myocardium [2831]. For example, Leong and colleagues have provided a general and versatile strategy by using transwell-mediated layering of endothelial cells and tissue cells for drug testing [30,31]. However, generating volumetric cardiac tissues containing embedded endothelial networks remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that hybrid materials of chitosan–gelatine–agarose with halloysite nanotubes may be ideal scaffolds for tissue engineering applications. The tissue‐engineered constructs can be more realistic models for testing bionanomaterials …”
Section: From Earth: Clay‐based Hybrid Nanoarchitectonicsmentioning
confidence: 99%